1990
DOI: 10.1007/bf00040298
|View full text |Cite
|
Sign up to set email alerts
|

Use of solid and gel state 13C NMR spectroscopy for differentiation between agarophytes and carrageenophytes

Abstract: Both solid state (CP-MAS) and gel state (using standard solution state conditions) 13 C NMR spectroscopy have been used to characterize a range of red algae that produce either agar or carrageenan . These techniques allow rapid determination of phycocolloid type within the algal tissue before extensive and time-consuming extractions and fractionations are carried out .The gel state technique can be used on living or dried material . Gel state spectra give high resolution and, because of the expectation that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Because of the typical low concentration of this type of residues in agars from Gracilaria further 1D 13 C attached proton tests (APTs) were performed with more scans than the previous 13 C spectra in order to check for the existence of typical signals of acetal C. No methyl, acetal, or carbonyl carbons could be detected in the APT spectrum (data not shown). Therefore, we concluded that no traceable amounts of pyruvated G segments existed in the extracts and that the signal around (1.30; 30) ppm could be related with nongalactan signals . No detectable starch contamination was found in native agars from IMTA seaweed (absence of typical C NMR signals of (1 → 4) (1 → 6)-α- d -glucan) contrary to wild G. vermiculophylla from French waters…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Because of the typical low concentration of this type of residues in agars from Gracilaria further 1D 13 C attached proton tests (APTs) were performed with more scans than the previous 13 C spectra in order to check for the existence of typical signals of acetal C. No methyl, acetal, or carbonyl carbons could be detected in the APT spectrum (data not shown). Therefore, we concluded that no traceable amounts of pyruvated G segments existed in the extracts and that the signal around (1.30; 30) ppm could be related with nongalactan signals . No detectable starch contamination was found in native agars from IMTA seaweed (absence of typical C NMR signals of (1 → 4) (1 → 6)-α- d -glucan) contrary to wild G. vermiculophylla from French waters…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, we concluded that no traceable amounts of pyruvated G segments existed in the extracts and that the signal around (1.30; 30) ppm could be related with nongalactan signals. 22 No detectable starch contamination was found in native agars from IMTA seaweed (absence of typical C NMR signals of (1 → 4) (1 → 6)-α-D-glucan) 4 contrary to wild G. vermiculophylla from French waters. 23 FTIR analysis showed typical bands of agar-like galactans and were well related with NMR results.…”
Section: ■ Materials and Methodsmentioning
confidence: 92%
“…-Carrageenan forms physical gels in vitro that mimic the conformational and physical properties of algal cell walls [51,52]. By definition, gels are not as well organised as highly crystalline materials such as cellulose, chitin or starch.…”
Section: Discussionmentioning
confidence: 99%
“…Several fucose-containing sulfated polysaccharides called fucoidans have been reported in brown algae and exhibited antioxidant or anti-inflammatory activities. , Agar units can also be sulfated or methylated at different positions, giving furcellaran, funoran, porphyran, and carrageaenan, which have been differentiated using 13 C ssNMR. Solid-state NMR has also been conducted to separate agars and carrageenans extracted from red algae …”
Section: The Highly Diverse Cell-wall Complexes Of Ubiquitous Algaementioning
confidence: 99%